2005
DOI: 10.1038/nn1541
|View full text |Cite
|
Sign up to set email alerts
|

Neural population coding of sound level adapts to stimulus statistics

Abstract: Mammals can hear sounds extending over a vast range of sound levels with remarkable accuracy. How auditory neurons code sound level over such a range is unclear; firing rates of individual neurons increase with sound level over only a very limited portion of the full range of hearing. We show that neurons in the auditory midbrain of the guinea pig adjust their responses to the mean, variance and more complex statistics of sound level distributions. We demonstrate that these adjustments improve the accuracy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
473
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(516 citation statements)
references
References 35 publications
38
473
5
Order By: Relevance
“…Speed sensitivity increased for some stimuli but decreased for others. Similar neuronal changes were found in other visual submodalities (34) and other sensory modalities (35).…”
Section: Discussionsupporting
confidence: 79%
“…Speed sensitivity increased for some stimuli but decreased for others. Similar neuronal changes were found in other visual submodalities (34) and other sensory modalities (35).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, although the frequency of bursting varies across stimuli, the high accuracy of feature detection remains constant. This stimulusdependent change in the response properties of AN2 is functionally similar to the adaptation that has been described in a number of sensory systems (Smirnakis et al, 1997;Kvale and Schreiner, 2004;Dean et al, 2005), which allows accurate detection and encoding of changes in a stimulus over a wide range of stimulus statistics.…”
Section: Discussionsupporting
confidence: 52%
“…The puzzling observation that this dynamic range decreases dramatically in noise has been called the "dynamic range problem" because behavioral results show that intensity changes are detectable up to high levels or in noise (e.g., Viemeister 1988). Recent data have shown that there may be dynamic range adaptation based on average sound intensity at various stages of the auditory pathway (Dean et al 2005;Wen et al 2009). The MOCR may be a mechanism contributing to this adaptation at an early stage in the auditory periphery.…”
Section: Bmentioning
confidence: 99%
“…This wide range occurs despite the fact that individual auditory neurons can change firing rates only over a limited range of levels. One way in which the auditory system may be able to accomplish this is through dynamic range adaptation (Dean et al 2005), which effectively shifts the dynamic range of neurons based on preceding acoustic stimulation. Some dynamic range adaptation may be produced by the medial olivocochlear reflex (MOCR) .…”
Section: Introductionmentioning
confidence: 99%